Designs for stained glass by Tobias Stimmer and artists of his circle in the State Hermitage - Sėpman, Natalʹja S. (Reports of the State Hermitage Museum, 2010)
Entwürfe von Stimmer, Christoph Murer (Werkstatt), Werner Kübler und Abraham Sybold.